2021
DOI: 10.1039/d1cc03887g
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic reduction of CO2 to CO and HCO2 with Zn(ii) complexes displaying cooperative ligand reduction

Abstract: Air-stable zinc(II) pyridyl phosphine complexes, [Zn(2-2,6-{Ph2PNMe}2(NC5H3)Br2] (1) [Zn(2-2-{Ph2PNMe}(NC5H3)Br2] (2) are reported and 1 was capable of electrocatalytic reduction of CO2 at -2.3 V vs. Fc+/0 to yield CO/HCO2H in mixed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Complex 2 is related to 1 by the replacement of the NMe moieties with NH groups. [36] The characterization of 2 through spectroscopic and single crystal diffraction methods compared well with 1. For example, the 1 H NMR spectrum of compound 2 was similar to that of 1 with the expected absence of the NÀ Me resonance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex 2 is related to 1 by the replacement of the NMe moieties with NH groups. [36] The characterization of 2 through spectroscopic and single crystal diffraction methods compared well with 1. For example, the 1 H NMR spectrum of compound 2 was similar to that of 1 with the expected absence of the NÀ Me resonance.…”
Section: Resultsmentioning
confidence: 99%
“…The results for the DFT optimization of [Zn(2,6-{Ph 2 PNMe} 2 (NC 5 H 3 ))Br 2 ] (1) have been previously reported. [36] An analogous approach was taken with [Zn(2,6-{Ph 2 PNH} 2 (NC 5 H 3 ))Br 2 ] (2) with optimization using the B3LYP functional, the def2TZVP basis set, and the polarized continuum model for solvation using acetonitrile. The absence of imaginary values in the frequency analysis confirmed that the resulting structure was a minimum.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest occupied molecular orbital (LUMO, MO88) was composed of a π * orbital of the bis(imino)pyridine portion of the ligand. This ligand‐based MO provides a means for the ligand to act as an electron reservoir for electrocatalysis [41] …”
Section: Resultsmentioning
confidence: 99%
“…This ligandbased MO provides a means for the ligand to act as an electron reservoir for electrocatalysis. [41] Computational optimization on both single and double reduction products (reductions at À 0.89 V and À 1.05 V) of 1 were also completed and the resulting structures and frontier orbitals are shown in Figures S23-S24. Isosurface plots for these species display similar features and vary only slightly in terms of MO contributions.…”
Section: Reductionmentioning
confidence: 99%
“…The electrocatalytic reduction of CO 2 to yield CO and HCO 2 − is a key process in the utilization of CO 2 as a C 1 source for further the synthesis of as a fuel. Air-stable Zn( ii ) pyridyl phosphine complexes, [Zn(κ 2 -2,6-{Ph 2 PNMe} 2 (NC 5 H 3 ))Br 2 ] and [Zn(κ 2 -2-{Ph 2 PNMe}(NC 5 H 3 ))Br 2 ] were reported in a paper by Berro et al , 243 and these were capable of the electrocatalytic reduction of CO 2 at −2.3 V vs. Fc +/0 to yield CO/HCO 2 H in mixed water/acetonitrile solutions. Their reactivity was attributed to a synergy between a reduced, basic ligand and the acidity of the Zn( ii ) center.…”
Section: The Zn-based Organic Catalystsmentioning
confidence: 98%